Resin bonding to root canal dentin: Effect of the application of an experimental hydrophobic resin coating after an all-in-one adhesive - Lombardo, Geraldo H. L. [UNESP]; Souza, Rodrigo O. A. [UNESP]; Michida, Silvia M. A. [UNESP]; De Melo, Renata Marques [UNESP]; Bottino, Marco Antonio [UNESP]; Valandro, Luiz Felipe (My University, 2008)
Aim: Based on the hypothesis the application of a low-viscosity hydrophobic resin coating improves the bond of all-in-one adhesive, the purpose of the study was to evaluate the bond strength of four adhesive systems to bovine root dentin using the push-out test method. Methods and Materials: The root canals of 32 bovine roots (16 mm) were prepared to a length of 12 mm using a FRC Postec Plus preparation drill. The specimens were allocated into four groups according to the adhesive system used: (Group 1) All-in-one Xeno III; (Group 2) All-in-one Xeno III+ScotchBond Multi-Purpose Plus Adhesive; (Group 3) Simplified Etch & Rinse One Step Plus; and (Group 4) Multi-Bottle Etch & Rinse All-Bond 2. A fiber-reinforced composite retention post was reproduced using an additional silicon impression and fabricated with DuoLink resin cement. The root specimens were treated with the selected adhesive systems, and the resin posts were luted in the canals with DuoLink resin cement. Each root specimen was cross sectioned into four samples (±1.8 mm in thickness), and the post sections were pushed-out to determine the bond strength to dentin. Results: Group 2 (2.9±1.2) was statistically higher than Group 1 (1.1±0.5) and Group 3 (1.1±0.5). Groups 1 and 3 showed no statistically significant difference while Group 4 (2.0±0.7) presented similar values (p>0.05) to Groups 1, 2, and 3 [(one-way analysis of variance (ANOVA)] and Tukey test, α=0.05). Conclusion: The hypothesis was accepted since the application of the additional layer of a low-viscosity bonding resin improved the bond of the all-in-one adhesive. Further studies must be conducted to evaluate the long-term bond.
Keywords: Adhesive systems; Bond strength; Push-out test; Root dentin; Simplified adhesive; All Bond 2; All-Bond 2; dentin bonding agent; Duo Link; Duo-Link; methacrylic acid derivative; ONE STEP PLUS; ONE-STEP PLUS; resin; resin cement; Scotchbond Multi Purpose Plus; Scotchbond Multi-Purpose Plus; Xeno III; adhesion; animal; cattle; chemistry; dental acid etching; dental bonding; dentin; endodontics; hydrophobicity; instrumentation; materials testing; mechanical stress; methodology; tooth crown; tooth pulp; ultrastructure; Acid Etching, Dental; Adhesiveness; Animals; Cattle; Composite Resins; Dental Bonding; Dental Pulp Cavity; Dentin; Dentin-Bonding Agents; Hydrophobicity; Materials Testing; Methacrylates; Post and Core Technique; Resin Cements; Root Canal Preparation; Stress, Mechanical